Living gender after communism - Johnson, Janet Elise; Robinson, Jean C. (Indiana University Press, 2007)
How has the collapse of communism across Europe and Eurasia changed gender? In addition to acknowledging the huge costs that fell heavily on women, Living Gender after Communism suggests that moving away from communism in Europe and Eurasia has provided an opportunity for gender to multiply, from varieties of neo-traditionalism to feminisms, from overt negotiation of femininity to denials of gender. This development,in turn, has enabled some women in the region to construct their own gendered ident
Keywords: Women : Europe : History : 20th century; Feminism : Europe : History : 20th century; Women : Europe : Social conditions : 20th century; Post-communism : Europe : History : 20th century